Large-scale genomic analysis of Elizabethkingia anophelis - Pavel Andriyanov; Pavel Zhurilov; Alena Menshikova; Anastasia Tutrina; Ivan Yashin; Daria Kashina (BMC Genomics)
Abstract The recent emergence of Elizabethkingia anophelis as a human pathogen is a major concern for global public health. This organism has the potential to cause severe infections and has inherent antimicrobial resistance. The potential for widespread outbreaks and rapid global spread highlights the critical importance of understanding the biology and transmission dynamics of this infectious agent. We performed a large-scale analysis of available 540 E. anophelis, including one novel strain isolated from raw milk and sequenced in this study. Pan-genome analysis revealed an open and diverse pan-genome in this species, characterized by the presence of many accessory genes. This suggests that the species has a high level of adaptability and can thrive in a variety of environments. Phylogenetic analysis has also revealed a complex population structure, with limited source-lineage correlation. We identified diverse antimicrobial resistance factors, including core-genome and accessory ones often associated with mobile genetic elements within specific lineages. Mobilome analysis revealed a dynamic landscape primarily composed of genetic islands, integrative and conjugative elements, prophage elements, and small portion of plasmids emphasizing a complex mechanism of horizontal gene transfer. Our study underscores the adaptability of E. anophelis, characterized by a diverse range of antimicrobial resistance genes, putative virulence factors, and genes enhancing fitness. This adaptability is also supported by the organism’s ability to acquire genetic material through horizontal gene transfer, primarily facilitated by mobile genetic elements such as integrative and conjugative elements (ICEs). The potential for rapid evolution of this emerging pathogen poses a significant challenge to public health efforts.